Pengintegrasian Nilai-nilai Imtaq dengan Media Grafis terhadap Hasil Belajar IPS Terpadu Siswa Kelas VIII SMPN 2 Jerowaru - Muhamad Zaril Gapari (ISLAMIKA, 2019)
The purpose of this study was to determine the integration of imtaq values ​​with graphic media in integrated social studies learning on student learning outcomes. This research was conducted at Jerowaru 2 Public High School in class VIII. The type of this research is experimental research, and in this study the independent variable is the integration of imtaq values ​​with graphic media and the dependent variable is student learning outcomes on the subject of demand and supply (buying and selling). While the research sample is class VIII-A as an experiment (using integration of imtaq values ​​with graphic media) and class VIII-B as a control class and the instrument used is an objective test consisting of 25 items. Based on the results of data analysis, obtained the average value of the group using the integration of imtaq values ​​with 58.86 graphic media and the group using integration of imtaq values ​​without the graphic media is 55.05 means that the use of integrating imtaq values ​​with graphic media can improve learning outcomes students. While the results of hypothesis testing obtained t-count is greater than t-table, namely 1.925> 1.684. This means that the proposed hypothesis is accepted (Ho rejected and Ha accepted), namely the use of integrating imtaq values ​​with graphic media more effectively to improve student learning outcomes when compared to those who do not use the integration of imtaq values ​​without graphic media in class VIII Jerowaru Junior High School 2.